2016
DOI: 10.1177/1464884916673387
|View full text |Cite
|
Sign up to set email alerts
|

Preaching to the choir? An analysis of newspaper readability vis-a-vis public literacy

Abstract: This study examined the interplay among readability, literacy, story type, and demographics in regard to the complexity of local newspaper content. Literacy data were derived from the US Census Bureau’s 2014 American Community Survey and readability data were derived from a content analysis of a random sample of 400 county level newspaper articles in Texas. Readability was measured dually by the Flesch–Kincaid grade reading level and the Flesch reading ease scale. On average, the news articles were written at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…In addition to education research, Flesch-Kincaid measures have been used in various others fields of study for a wide variety of research questions. In journalism research, a recent study shows that newspaper articles tend to be so complex that they are hardly understandable for a majority of readers [37]. Political scientists have found that people are less likely to vote on ballots that have more complex language [38].…”
Section: Methodsmentioning
confidence: 99%
“…In addition to education research, Flesch-Kincaid measures have been used in various others fields of study for a wide variety of research questions. In journalism research, a recent study shows that newspaper articles tend to be so complex that they are hardly understandable for a majority of readers [37]. Political scientists have found that people are less likely to vote on ballots that have more complex language [38].…”
Section: Methodsmentioning
confidence: 99%
“…Even if their validity is questioned, as can be done on many grounds, there is still a comparative viewpoint supporting the conclusion of overall complexity. For instance, local newspapers in the United States have been observed to attain values around 12 at maximum [38]. Another comparative example would be abstracts in psychology papers for which values around 17 have been reported [39].…”
Section: Resultsmentioning
confidence: 99%
“…This study set out to show that audiences valued comprehensibility as a factor of credibility perception; however, the results here indicate that is not the case. In his study of media literacy, Wasike (2018) calls for use of automated readability tests as part of the editing process so as to make the news more engaging and less discouraging for readers, suggesting that difficult-to-read content might be exacerbating supposed declines in written news credibility and trust. To the contrary, this study suggests that might not be the case.…”
Section: Discussionmentioning
confidence: 99%